1986
DOI: 10.1177/096032718600500407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Purgatives on Antidotal Efficacy of Oral Activated Charcoal

Abstract: 1 The effects of purgatives on the antidotal efficacy of oral activated charcoal were studied in seven volunteer subjects. 2 The volunteer subjects were given 1000 mg of aspirin, 100 mg of atenolol and 50 mg of phenylpropanolamine with 100 ml of water on an empty stomach and were assigned randomly to the following treatment groups: (A) after 5 min 150 ml of water, (B) after 5 min 25 g of charcoal, (C) after 5 min charcoal orally with 20 mg of metoclopramide rectally, followed by 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We then evaluated whether or not the adsorption of APAP and NAC onto AC competed with each other. Because the gastrointestinal transit time of AC was about 7 h, 11) NAC was added to the AC and APAP mixed suspension in 3 parts corresponding to the loading dose and 2 times of the maintenance doses. The adsorption rate of APAP with NAC in SGF was ≥97.88%, and that in SIF was 99.00%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then evaluated whether or not the adsorption of APAP and NAC onto AC competed with each other. Because the gastrointestinal transit time of AC was about 7 h, 11) NAC was added to the AC and APAP mixed suspension in 3 parts corresponding to the loading dose and 2 times of the maintenance doses. The adsorption rate of APAP with NAC in SGF was ≥97.88%, and that in SIF was 99.00%.…”
Section: Resultsmentioning
confidence: 99%
“…10) However, the transit time of AC is several hours, even though a cathartic is given with the AC to enhance the elimination of the charcoal-poisoning complex. 11,12) If AC stays in the stomach and intestines, the NAC would likely be adsorbed onto the AC. The objective of this study was to evaluate the effect of AC on a 72-h oral regimen of NAC using in vitro methods.…”
Section: Introductionmentioning
confidence: 99%
“…Klaus Olkkola, at present the Professor and Chairman of Anaesthesiology, Intensive Care, Emergency Care, and Pain Medicine at the University of Turku, Finland, started his scientific career as my first doctoral student by studying factors affecting the antidotal efficacy of activated charcoal. In these systematic studies, we explored the effect of charcoal dose , gastric contents , ethanol and gastric pH , and purgatives on the charcoal′s antidotal efficacy and confirmed the superiority of charcoal over ipecac in gastrointestinal decontamination .…”
Section: Activated Charcoal As An Antidotementioning
confidence: 86%
“…This overdose may have been fatal if EGD decontamination was not performed. Studies have shown atenolol, lisinopril, and chlorthalidone bind to charcoal [19], but there are not studies showing improved patient outcomes with its use. Charcoal alone is unlikely to have provided the same amount of benefit based on the quantity adhered to the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%